Triangle of Cyber, Terrorism and Radicalization - KAPU, Sevde (Cyberpolitik Journal, 2021)
Cyberspace, called the new field of terrorism, is a transition zone from traditional terrorism to cyber-terrorism. The concept of cyber terrorism created by the combination of the words cyber and terrorism that generates a great risk environment in a world that is increasingly dependent on technology. Terrorist groups that take advantage of the opportunities for unlimited, anonymous and low-cost cyberspace are easily adapted to cyberspace and try to achieve their goals of radicalization through methods such as propaganda and recruitment. In a digitized world, it is possible that terrorist organizations will gain strength and endanger the national security of states by carrying out major cyber attacks.